1989
DOI: 10.1128/jb.171.12.6503-6510.1989
|View full text |Cite
|
Sign up to set email alerts
|

Transcription from the P1 promoters of Micromonospora echinospora in the absence of native upstream DNA sequences

Abstract: We demonstrated previously that the 0.4-kilobase DNA fragment from Micromonospora echinospora contains multiple tandem promoters, Pla, Plb, Plc, and P2, which are also functional when cloned into Streptomyces lividans. We now show by in vitro transcription with Streptomyces RNA polymerase that each of these promoters is an authentic initiation site, rather than a processing site for transcripts which initiate further upstream. The DNA sequence requirements for the closely spaced promoters Pla, Plb, and Plc, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Perhaps the closest analogous promoters are P1a and P1b from M. echinospora. Baum et al (2,3) have shown that P1a and P1b do not require native DNA further than 5 and 20 bp upstream from the transcription start point, respectively. There are some intriguing parallels between these M. echinospora promoters and the sapA promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the closest analogous promoters are P1a and P1b from M. echinospora. Baum et al (2,3) have shown that P1a and P1b do not require native DNA further than 5 and 20 bp upstream from the transcription start point, respectively. There are some intriguing parallels between these M. echinospora promoters and the sapA promoter.…”
Section: Discussionmentioning
confidence: 99%
“…5, lane 1). In contrast, when RNA was isolated from the isogenic strain containing the 0.4-kb insert within plasmid pPP14 (lane 2), transcripts Pla, Plb, Plc, Ptk, and P2 were detected, as observed previously (1,2). The start site of each promoter has also been determined by using dinucleotides to prime transcriptional runoff assays with Streptomyces RNA polymerase (1).…”
Section: Methodsmentioning
confidence: 99%
“…Second, the Pla and Plb promoters lack upstream sequence requirements; i.e., they function in S. lividans even if native DNA sequences are replaced just 5 nucleotides before the Pla start site and 20 nucleotides before the Plb start site. In contrast, transcription from the Plc promoter located downstream of Plb is diminished in activity as a result of these substitutions 35 nucleotides upstream of its start site (1). The Plc promoter therefore appears to resemble many Escherichia coli promoters in requiring sequences that extend to at least 40 nucleotides upstream of transcriptional initiation (19).…”
mentioning
confidence: 97%
See 2 more Smart Citations